PENINGKATAN PENGETAHUAN MASYARAKAT MELALUI PENYULUHAN DENGAN TEMA MENGENAL STUNTING LEBIH DALAM DI POSYANDU KELURAHAN BELIAN KOTA BATAM - Ulpawati Ulpawati; Novi Yulianti; Susanti Susanti (Nusantara Hasana Journal, 2022)
Stunting is a failure to grow in children or toddlers due to chronic malnutrition. Stunting can affect intelligence and cognitive abilities in children. The problem faced is the low understanding and knowledge of the community about stunting. Objectives Increase public knowledge and understanding of stunting and the signs and symptoms of stunting. The counseling activity was attended by 63 participants who are community stakeholders in the working area of ​​Belian Village, Batam City. The counseling was also followed by routine measurement activities for toddlers, namely measuring weight and height and giving monthly vaccines. The action location was held at the posyandu, Belian sub-district, Batam city; in addition to counseling in the form of lectures, the team also displayed videos related to stunting events so that the public could illustrate the impact of stunting events. The counseling activities carried out went smoothly according to the plan, and the community's enthusiasm was evident from the continuous question and answer discussions with the participants and presenters. The need for follow-up activities in hinterland areas with the reason that these areas are tough to access health services, and transportation is difficult due to the position of the population on small islands.